Working hours mismatch and well-being: comparative evidence from Australian and German panel data - Christoph Wunder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This study uses subjective measures of well-being to analyze how workers perceive working hours mismatch. Our particular interest is in the question of whether workers perceive hours of underemployment differently from hours of overemployment. Previous evidence on this issue is ambiguous. We call attention to the level of well-being in the absence of hours mismatch that serves as a reference state for comparison purposes and to the consequences of restrictive functional form assumptions. Using panel data from Australia and Germany, this study estimates the relationship between working hours mismatch and well-being as a bivariate smooth function of desired hours and mismatch hours by tensor product p-splines. The results indicate that well-being is highest in the absence of hours mismatch. In general, the perception of overemployment is statistically significantly different from the perception of underemployment in both countries. In Australia, workers tolerate some underemployment, as their well-being tends to be unaltered in the presence of short hours of underemployment. However, the marginal loss from underemployment appears to be larger than that from overemployment once the mismatch exceeds approximately ten hours. In Germany, on the contrary, underemployment is clearly more detrimental for well-being than overemployment. German males with preferences for full-time hours hardly respond to overemployment.
Keywords: I31; J21; J22; 330